Application block word for android user - Mohd Amirul Amzar, Mohd Talib (2019)
Nowadays, the mobile phone plays a major role in our lives, which brings many benefits to us but also contains some drawbacks. The mobile phone will certainly bring about a lot of advantages. First of all, the mobile phone can well-thought-out the swiftest means of communication in our daily life. We can contact easily with our anyone by calling or sending messages. It can also made people happier in daily live with entertainment. For example, listen to music and play games on mobile phone. Moreover, by using the latest apps for smartphones, accessing to internet looking Film and check our profile in social networks. Our studying becomes more effective and easier by having current smartphone in hand which can makes look up dictionary, find out many source of reference on internet for useful of studying.